Competitive Advantage as a Mediator of Business Resilience: An Analysis of Digital Adaptability and Financial Capabilities of Yogyakarta Culinary MSMEs - Arief Nurrahman; Muhammad Harfiansyah Makarim; Caesar Rosyad Achmadi; Agatha Saputri; R. Andro Zylio Nugraha (Universitas Negeri Yogyakarta, 2026)
Economic uncertainty requires Micro, Small, and Medium Enterprises (MSMEs) to demonstrate high endurance. This study aims to analyze the impact of digital adaptability and financial capabilities on business resilience and to examine the role of competitive advantage as a mediating variable among traditional culinary MSMEs in the Special Region of Yogyakarta. A quantitative explanatory approach was employed, with primary data collected via questionnaires distributed to 87 culinary MSME owners. The sampling was conducted using a purposive sampling technique. Data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method in SmartPLS 4. The empirical results reveal that the structural model possesses strong predictive power, explaining 77.5% of the variance in business resilience. Specifically, the findings indicate that both digital adaptability and financial capabilities have a positive and significant direct effect on competitive advantage and business resilience. Furthermore, the mediation analysis confirms that competitive advantage serves as a significant partial mediator in the relationship between both digital and financial capabilities toward business resilience. These findings conclude that merely adopting technology and maintaining financial discipline are insufficient; these resources must be strategically leveraged to create a distinct competitive advantage for MSMEs to survive and thrive in the era of disruption. The practical implications of this study provide strategic guidance for MSME practitioners and local governments in designing economic recovery programs focused on strategic value creation rather than basic digital onboarding.